1999
DOI: 10.1093/humrep/14.11.2755
|View full text |Cite
|
Sign up to set email alerts
|

Donor age is paramount to success in oocyte donation *

Abstract: Several reports suggest increasing age in oocyte donors decreases the chances of in-vitro fertilization (IVF) success, while others describe no effect. The published data concerning gravidity and parity are similarly conflicting. To further address these questions, we retrospectively studied 445 consecutive donor IVF cycles at two large university-based IVF practices. Donor cycles were analysed for the number of oocytes retrieved, gravidity, parity, and age of the donor, and pregnancy outcome in recipients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 21 publications
0
26
0
4
Order By: Relevance
“…One of the most important issues in an egg donor program is to have a good screening protocol, where only potentially successful donors are accepted into the program. Unfortunately, this is not an easy task and studies showed that selecting only young donors, [16,17] failed to show any variables that would make a difference in future outcome [18][19][20]. In our program, we include donors younger than 35 years old with regular menses, with normal basal FSH/estradiol levels and basal antral follicle count, without androgenic characteristics, and without history of repeated spontaneous miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important issues in an egg donor program is to have a good screening protocol, where only potentially successful donors are accepted into the program. Unfortunately, this is not an easy task and studies showed that selecting only young donors, [16,17] failed to show any variables that would make a difference in future outcome [18][19][20]. In our program, we include donors younger than 35 years old with regular menses, with normal basal FSH/estradiol levels and basal antral follicle count, without androgenic characteristics, and without history of repeated spontaneous miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…Data from egg-donation programs have shown that the quality of human oocytes decreases with the age of the donor (17). Little is known about the mechanism (but see ref.…”
Section: Significancementioning
confidence: 99%
“…To date the majority of published studies are of a retrospective nature analyzing a more or less large consecutive series of recipients. The most studied prognostic factors include donor and recipient age, oocyte donation indication, endometrial thickness, and duration of estrogen replacement (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%